2006
DOI: 10.1007/s00467-006-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ambulatory blood pressure monitoring in children and adolescents

Abstract: Diagnosis of hypertension is critically dependent on accurate blood pressure measurement. "Accurate" refers to carefully following the guidelines for blood pressure measurement laid out for children and adults to minimize observer and subject errors that commonly occur in clinical blood pressure measurement. Accurate blood pressure measurement is more important in children and adolescents as the misdiagnosis of hypertension may have a life-long adverse impact on insurability and employment. Automated blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 133 publications
(98 reference statements)
5
36
1
2
Order By: Relevance
“…Methods used for BP measurement varied among studies in our meta-analysis; they included manual sphygmomanometers, as well as automated devices, which have the advantage of achieving high-quality BP determinations by reducing observer errors [64]. In three studies, the method used for BP measurement was not stated.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used for BP measurement varied among studies in our meta-analysis; they included manual sphygmomanometers, as well as automated devices, which have the advantage of achieving high-quality BP determinations by reducing observer errors [64]. In three studies, the method used for BP measurement was not stated.…”
Section: Discussionmentioning
confidence: 99%
“…Renal scarring is a well-known cause for hypertension and proteinuria, with progression to end-stage renal disease (ESRD) in some pediatric patients [12,13]. The 24-h ambulatory blood pressure monitoring (ABPM) is being increasingly used in children with renal disease, including those with scarring [14]. In a study published by Milosevski et al, ABPM demonstrated nocturnal systolic hypertension in all patients with renal scarring [15].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 This statement summarizes the current research and clinical applications of ABPM in children and adolescents and offers recommendations on implementation of ABPM in practice and interpretation of results. Because no outcome studies are yet available relating ABPM levels in children to hard outcomes such as myocardial infarction or stroke, these guidelines are expert opinion-driven and not evidence based.…”
Section: Epidemiology Of Hypertensionmentioning
confidence: 99%
“…12 In these patients, ABPM can be very helpful in stratifying risk for target organ damage, because even with normal average ABPM values, increased BP variability is associated with target organ damage in adults. 52 This may be especially relevant if there is a strong family history of hypertension, because BP variance is under substantial genetic control.…”
Section: Prehypertensionmentioning
confidence: 99%